Changes in Brazilian Drosophilidae (Diptera) assemblages across an urbanisation gradient - Gottschalk, Marco S.(Univ. Federal do Rio Grande do Sul Depto. Genética Lab. de Drosophila); De Toni, Daniela C.(Univ. Federal de Santa Catarina Depto. Biologia Celular, Embriologia e Genética Lab. de Drosofilídeos); Valente, Vera L.S.(Univ. Federal do Rio Grande do Sul Depto. Genética Lab. de Drosophila,Univ. Federal do Rio Grande do Sul Programa de Pós-Graduação em Biologia Animal); Hofmann, Paulo R.P.(Univ. Federal de Santa Catarina Depto. Biologia Celular, Embriologia e Genética Lab. de Drosofilídeos) (Neotropical entomology, 2007)
The present study aims to characterise the assemblages of Drosophilidae sampled from four sites subject to different levels of urbanisation, in the city of Florianópolis, South Brazil. Five samples were collected between August 2000 and August 2001 and five between August 2002 and August 2003 in each site. A gradual change in the dominant species was observed in the urbanisation gradient, with an increase in relative abundance of exotic species in urban areas. Among the native species, the relative abundance of Drosophila capricorni Dobzhansky & Pavan had an expressive decrease. In the other hand the richness in the low urbanisation site increased, probably due to the presence of urban gardens. The diversity index did not vary significantly among sites, but its correlation with evenness and richness changed. O presente estudo objetiva caracterizar as assembléias de Drosophilidae amostradas em quatro pontos sujeitos a diferentes níveis de urbanização, na cidade de Florianópolis, Sul do Brasil. Foram realizadas cinco amostragens entre agosto/2000 e agosto/2001 e cinco entre agosto/2002 e agosto/2003 em cada ponto. Uma mudança gradual nas espécies dominantes foi observada no gradiente de urbanização, com acréscimo na abundância relativa das espécies exóticas nas áreas urbanas. Entre as espécies nativas, houve um decréscimo expressivo na abundância relativa de Drosophila capricorni Dobzhansky & Pavan. Por outro lado, a riqueza no ponto de baixa urbanização aumentou, provavelmente devido à presença de áreas verdes na cidade. O índice de diversidade não variou significativamente entre os pontos, mas sua correlação com a eqüitabilidade e a riqueza se alterou.